Climate change mitigation and agriculture - Wollenberg, Eva Karoline; Tapio-Bistrom, M.L.; Grieg-Gran, M.; Nihart, A (Earthscan, 2011)
This book reviews the state of agricultural climate change mitigation globally, with a focus on identifying the feasibility, opportunities and challenges for achieving mitigation among smallholder farmers. The purpose is ultimately to accelerate efforts towards mitigating land-based climate change. While much attention has been focused on forestry for its reputed cost-effectiveness, the agricultural sector contributes about ten to twelve per cent of emissions and has a large technical and economic potential for reducing greenhouse gases. The book does not dwell on the science of emissions reduction, as this is well covered elsewhere; rather, it focuses on the design and practical implementation of mitigation activities through changing farming systems.